Oxygen isotopic composition of coarse- and fine-grained material from comet 81P/Wild 2. (1st October 2015) - Ogliore, Ryan C.; Nagashima, Kazuhide; Huss, Gary R.; Westphal, Andrew J.; Gainsforth, Zack; Butterworth, Anna L.
Abstract: Individual particles from comet 81P/Wild 2 collected by NASA's Stardust mission vary in size from small sub-μm fragments found in the walls of the aerogel tracks, to large fragments up to tens of μm in size found towards the termini of tracks. The comet, in an orbit beyond Neptune since its formation, retains an intact a record of early-Solar-System processes that was compromised in asteroidal samples by heating and aqueous alteration. We measured the O isotopic composition of seven Stardust fragments larger than ∼2 μm extracted from five different Stardust aerogel tracks, and 63 particles smaller than ∼2 μm from the wall of a Stardust track. The larger particles show a relatively narrow range of O isotopic compositions that is consistent with 16 O-poor phases commonly seen in meteorites. Many of the larger Stardust fragments studied so far have chondrule-like mineralogy which is consistent with formation in the inner Solar System. The fine-grained material shows a very broad range of O isotopic compositions (−70‰ <  Δ 17 O < +60‰) suggesting that Wild 2 fines are either primitive outer-nebula dust or a very diverse sampling of inner Solar System compositional reservoirs that accreted along with a large number of inner-Solar-System rocks to form comet Wild 2.